Lung cancer : principles and practice - Pass, Harvey I. (Lippincott Williams & Wilkins, 2005)
"A comprehensive review of lung cancer, from screening, early detection, and prevention, to management strategies including surgery, chemotherapy, radiation therapy, and multimodality therapy, as well as novel therapeutic strategies, palliation and special considerations, and other thoracic tumors"--Provided by publisher.